(3GdeMeOhf ef GdTYQGA hCTYGQges - (3Ydj Hf jhSa Hf EHQGgje GdTjHGfj GdbaWj, CHh GdMSf, LeGd GdOjf,J (B646 (3g` s
(3ChdgG (B:s
(3Chd eG ajg JQLeI eMeO Hf CMeO GdQbi s
(3BNQgG (B:s
(3jfJgi Edi MQa GdSjf ef GdBHGA s
(3GdehLhO efg LRA jfJgi Edi MQa GdSjfi ef GdBHGAs
(3GfXQ Qbe (B446 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B263s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B325 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B258 s
Keywords: (3GdJGQjNs